Search for chameleons with CAST - V. Anastassopoulos; M. Arik; S. Aune; K. Barth; A. Belov; H. Bräuninger; G. Cantatore; J.M. Carmona; S.A. Cetin; F. Christensen; J.I. Collar; T. Dafni; et al. (Physics Letters B, 2015)
In this work we present a search for (solar) chameleons with the CERN Axion Solar Telescope (CAST). This novel experimental technique, in the field of dark energy research, exploits both the chameleon coupling to matter (βm) and to photons (βγ) via the Primakoff effect. By reducing the X-ray detection energy threshold used for axions from 1 keV to 400 eV CAST became sensitive to the converted solar chameleon spectrum which peaks around 600 eV. Even though we have not observed any excess above background, we can provide a 95% C.L. limit for the coupling strength of chameleons to photons of βγ≲1011 for 1<βm<106.